The Influence of Body Mass Index, Hemoglobin, and Blood Pressure on VO₂max of Elite-Pro Karatekas in South Sulawesi - Same, Rahyuddin Jide; Mahyuddin, Reza; Dahlan, Firmansyah; Zainuddin, Zainal Abidin (JOSSAE (Journal of Sport Science and Education), 2025)
The lack of knowledge regarding the physical health aspects of karate athletes prompted this study, which examines direct and indirect causal relationships between Body Mass Index (BMI), Hemoglobin (Hb), and Blood Pressure (BP) on the VO₂max of Elite-Pro Karatekas. Path analysis was employed with BMI (X1) and Hb (X2) as independent variables, BP (X3) as an intervening variable, and VO₂max (Y) as the dependent variable. Data were collected through BMI (height and weight), Hb (Easy Touch GCHB test), BP (digital sphygmomanometer), and VO₂max (Bleep Test). Results showed BMI affects BP (r=0.267, p=0.036), and Hb strongly affects BP (r=0.687, p=0.000), indicating more ideal Hb leads to more ideal BP. BMI also influences VO₂max (r=0.467, p=0.000), especially in overweight or high-BMI athletes with high muscle mass. Hb affects VO₂max (r=0.551, p=0.000), and BP also impacts VO₂max (r=0.505, p=0.000). Indirect effects were stronger: BMI affects VO₂max through BP (0.601>0.467) and Hb through BP (0.897>0.551). Karate coaching should emphasize nutrition, regular health monitoring of BMI, Hb, and BP, and reconsider excessive training habits. A deeper understanding of these health aspects can enhance athlete performance and reduce health risks.